Association Between Polymorphisms of DRD2, COMT, DBH, and MAO-A Genes and Migraine Susceptibility: A Meta-Analysis. Issue 47 (November 2015) - Chen, Hu; Ji, Chun-Xue; Zhao, Lian-Li; Kong, Xiang-Jun; Zeng, Xian-Tao
Abstract : Abstract: Some epidemiological studies have investigated the relationship between genetic polymorphisms of DRD2, COMT, DBH, and MAO-A and migraine susceptibility, but the results are still inconsistent. Thus, our aim was to further assess the association through a meta-analysis. We examined 5 single nucleotide polymorphisms (SNPs) in 4 genes, including DRD2 rs1799732 and rs6275, DBH rs7239728, MAI-A -VNTR, and COMT rs4680, and performed a meta-analysis of 11 published case–control studies including 3138 cases and 4126 controls. Odd ratios (ORs) with 95% confidence intervals (95% CIs) were used to evaluate the association between the 5 genetic polymorphisms and migraine susceptibility. There was no significant relationship between migraine susceptibility and 4 genetic polymorphisms of DRD2 rs1799732 and rs6275, DBH rs7239728, and MAO-A -VNTR. Nevertheless, decreased risk of migraine was observed to be in association with COMT rs4680 polymorphism in overall analysis (AA vs. GG + GA: OR = 0.76, 95% CI = 0.60–0.97, P Het  > 0.642, I 2  = 0), and in Caucasian group after subgroup analysis (AA vs. GG + GA: OR = 0.75, 95% CI = 0.58–0.96, P Het  > 0.433, I 2  = 0). Studied polymorphisms of DRD2, DBH, and MAO-A genes may not be associated with migraine susceptibility. However, COMT rs4680 polymorphism may decrease the risk of migraine, especially in Caucasians. The failure to evaluate environmental influence and provide adjusted effect size estimates highlights the need for additional studies in a large number to take these factors into consideration, thus better elucidating the role of the genes tested in migraine. Abstract : Supplemental Digital Content is available in the text